Esselen Linguistic Materials - Shaul, David L.; Turner, Katherine; Collins, James D. (Kansas Working Papers in Linguistics, 1984)
The primary purpose of this paper is to makea complete list of materials known on the Esselen language available in a single place. The existing lexical material has been organized into a lexicon which is followed by phrasal and sentence materials arranged by collector. This will allow the reader to evaluate the grammatical discussion in Kroeber (1904) Harrington (1913;published in Turner and Shaul 1981), Beeler (1978) and Shaul 1982).